Belief Model (Hbm) of Via on Childbearing Women in Lubuk Buaya Primary Health Centre in 2017 - Harridhil Silmi; Andi Friadi; Lisma Evareny (Universitas Andalas, 2017)
Cervical Cancer is the cancer with the second highest rate in Indonesian women and Awareness of childbearing women to Visual Inspection with Acetic Acid (VIA) is still low so often cause death in women. This study aims to determine the Health Beliefs Model (HBM) of VIA on childbearing women in Lubuk Buaya primary health centre 2017.This study was an analytic observational study with cross sectional design, conducted from August - Sept 2017 took 98 respondents as the sample. Data were collected by using questionnaire. Data analysis was performed by using univariate and bivariate.The results showed that there was a significant relationship between education (p=0,001), perceived susceptibility (p=0,000), perceived seriousness (p=0,000), health motivation (p=0,000), perceived benefits (p=0,000), and perceived barriers (p=0,000), with action cervical cancer early detection with VIA methods. There is a relationship between education, perceived susceptibility, perceived seriousness, health motivation perceived benefits, and perceived barriers to early detection of cervical cancer action with VIA methods on childbearing women in Padang Pasir primary health centre 2017. Suggested to Lubuk Buaya primary health centre to increase further dissemination and health promotion of cervical cancer early detection with VIA method through counseling about the importance of early detection with VIA method.